Influence of Early Enteral Nutrition on Clinical Outcomes in Neurocritical Care Patients With Intracerebral Hemorrhage - Peng, Jianhua; Volbers, Bastian; Sprugel, Maximilian I.; Hölter, Philip; Engelhorn, Tobias; Jiang, Yong; Kuramatsu, Joji; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Gerner, Stefan (Frontiers in Neurology, 2021)
Objective: Early enteral nutrition (EEN) represents the current standard of care for patients treated in general intensive care units (ICU). Specific nutritional recommendations for patients receiving dedicated neurocritical care are not established. This study investigated associations of EEN with clinical outcomes for patients suffering from intracerebral hemorrhage treated at a neurological ICU (NICU).
CRIS-Team WoS Importer:2021-05-14